1D and Q2D thermal resistance analysis of micro channel structure and flat plate heat pipe. (May 2017) - Chen, Shao-Wen; Chiu, Wan-June; Lin, Min-Song; Kuo, Feng-Jiun; Chai, Min-Lun; Lee, Jin-Der; Wang, Jong-Rong; Lin, Hao-Tzu; Lin, Wei-Keng; Shih, Chunkuan
Abstract: Heat pipes and two-phase heat transfer devices are widely used in electronics cooling, and the thermal resistance is a key issue to ensure the system performance and reliability. In this study, the traditional one dimensional (1D) and quasi-two dimensional (Q2D) methods were utilized to analyze the thermal resistance of the previous boiling experiments of evaporator tests with silicon (Si) and copper (Cu) micro channel structures as well as the existing flat-plate heat pipe tests with aluminum micro channels as wick structures. The temperature distributions and variations under different test conditions were collected, and the 1D and Q2D methods were applied to calculate the overall thermal resistance for evaporator tests and heat pipe tests and compared with the experimental data. The results showed that the Q2D method can predict the overall thermal resistance for the evaporator region and the whole heat pipe with a higher accuracy because the spreading resistance was significant and should be considered under small heater area (hot spot) conditions. Detailed distributions of thermal resistance and the calculated errors of each test sample under different heat loads were presented and compared. For present tests, the Q2D method can reach a lower average error (about 10%) and is recommended for calculations. Furthermore, the spreading resistance of Q2D method is further applied to calculate the selected test cases to investigate the wall thickness effects. The spreading resistance of the selected evaporator tests and heat pipe tests may decrease and increase, respectively, as wall thickness increases due to different evaporative heat transfer conditions. The present results demonstrate the applicability of the Q2D methods for both evaporator and heat pipe tests, and the present analyses can be a reference for future thermal management and electronic cooling designs. Highlights: 1D and Q2D thermal resistance analyses have been carried out for micro channel (evaporator) tests and heat pipe tests Experimental data of evaporator and heat pipe tests were collected for benchmark Detailed thermal resistance distributions have been compared The Q2D method has been validated and recommended for thermal analysis Wall thickness effect has been analyzed for selected test conditions